Digital Transformation for the Future of the Manufacturing Industry in Merauke Regency - Caecilia Henny; Okto Irianto; Mensy Otelyo Kastanya; Harmiza Erziena (AIBPM Publisher, 2026)
ABSTRACT This study aims to examine the opportunities, challenges, and strategies for implementing digital transformation in Merauke's manufacturing sector. A qualitative descriptive approach is applied, using literature review, policy analysis, and relevant studies on industrial digitalization. The findings indicate that technologies such as Internet of Things (IoT), Artificial Intelligence (AI), cloud computing, big data analytics, and automation significantly improve production efficiency, product quality, and industrial competitiveness while expanding market access through digital platforms and e-commerce. Effective implementation requires strong collaboration among government, industry, educational institutions, and local communities. Keywords: digital transformation, manufacturing industry, Industry 4.0, Merauke, smart manufacturing